2021
DOI: 10.1007/s13353-021-00641-4
|View full text |Cite
|
Sign up to set email alerts
|

Searching for new molecular markers for cells obtained from abdominal aortic aneurysm

Abstract: The aim of the study was to investigate specific potential markers for cells obtained from three layers of human AAA divided into three segments along the AAA based on morphological differences. The isolated cells were compared to control commercial cell types from healthy human abdominal aortas. For each type of aortic layer, three specimens from 6 patients were compared. Total RNA was isolated from 36 cell cultures for gene expression profiling and potential new cytometry markers were typed. Isolated cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…In addition, noncoding RNAs such as microRNA are biological molecules whose expression can be modified through targeted mechanisms and present opportunities to identify new treatment options for patients with aortic disease. 1-7 In addition, developing image-based cardiac and aortic markers derived from large-scale imaging studies with automated machine learning–based analysis might provide a wealth of information for guiding the optimal care of these patients.…”
Section: Evidence Gaps and Future Directionsmentioning
confidence: 99%
“…In addition, noncoding RNAs such as microRNA are biological molecules whose expression can be modified through targeted mechanisms and present opportunities to identify new treatment options for patients with aortic disease. 1-7 In addition, developing image-based cardiac and aortic markers derived from large-scale imaging studies with automated machine learning–based analysis might provide a wealth of information for guiding the optimal care of these patients.…”
Section: Evidence Gaps and Future Directionsmentioning
confidence: 99%
“…Infiltration of macrophages is associated with increased activity of matrix metalloproteinases 2 and 9, which lead to degradation of the ECM and weaken the aneurysmal wall [26]. In our recent studies, we have shown elevated expression of genes associated with the inflammation process in AAA, e.g., CD68, IL1R2 [10,27]. Flow cytometry of cells from the EL of AAA showed that these cells are positive for CD90 and anti-fibroblast marker, but their numbers were much lower compared with controls.…”
Section: Cd68mentioning
confidence: 95%
“…The phenotypes of the cells were determined by fluorescence-assisted flow cytometry using the Facs Aria I instrument (Becton Dickinson, Franklin Lakes, NJ, USA) as described in detail elsewhere [10]. For…”
Section: Fluorescence-assisted Cell Flow Cytometry Analysismentioning
confidence: 99%
“…AAA is a complex disease, and each case is slightly different [ 82 ]. This phenomenon is due to various factors such as environmental, genetic, and molecular.…”
Section: Conclusion/perspectivesmentioning
confidence: 99%
“…Extracellular matrix degradation and inflammation are considered to be the most important molecular processes contributing to AAA formation. The initiating molecular processes cause matrix degradation, cell apoptosis, and aging, as well as infiltration of inflammatory cells such as lymphocytes, mast cells, and neutrophils ( Figure 5 ) [ 82 , 83 , 84 ].…”
Section: Conclusion/perspectivesmentioning
confidence: 99%